Pretense as Creative Hallucination - West, Donna E. E. (Respectus Philologicus, 2016)
Ch. S. Peirce’s concept of “creative hallucination” (EP 2:192 1903) captures the myriad ways in which sterile conventional practices can be informed by word and role play. Word and person substitutions constitute not errors of judgment, but attain the status of metaphor, would-be propositions, and cultural myth. Naming practices come to represent instances of word play, in which metaphor and myth permeate new object identities, which, in turn reveal cultural dispositions. Accordingly, these newly conceived action habits express analogies of another to another other – illustrating potentialities for filling slots in role-play scenarios. In short, different cultures develop creative action-habits from distinctive mechanisms according to culturally driven processes, but they all culminate in representational diversity, by persons/entities becoming another. These creative hallucinations supply iconic and indexical scaffolds to supersede literal word use, and conventional person identities. But for the holistic parameters which nascent envisionment provides, the painter’s hunch that changing the colour to enhance the product may never have arisen.